Injection mold design engineering - Kazmer, David (Hanser ; Hanser Gardner, 2007)
"This book provides a vision and structure to finally synergize all the engineering disciplines that converge in the mold design process. The topics are presented in a top-down manner, beginning with introductory definitions and the>>big picture<<before proceeding to layout and detailed design of molds. The book provides very pragmatic analysis with worked examples that can be readily adapted to>>real world<<mold design-applications. It should help students and practitioners to understand the inner workings of injection molds and encourage them to think>>outside the box<<in developing innovative and highly functional mold designs."--Jacket